2000
DOI: 10.1016/s1010-7940(00)00368-7
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation after coronary artery bypass grafting without cardiopulmonary bypass

Abstract: Atrial fibrillation is a common complication after procedures of myocardial revascularization, performed with or without cardiopulmonary bypass. The occurrence is not dependent on the type of operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 14 publications
1
31
0
4
Order By: Relevance
“…However, some studies have shown that off-pump CABG does not change the incidence of postoperative AF compared with traditional CABG. 18,19 It is still unclear whether off-pump procedures result in a lower incidence of postoperative AF.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that off-pump CABG does not change the incidence of postoperative AF compared with traditional CABG. 18,19 It is still unclear whether off-pump procedures result in a lower incidence of postoperative AF.…”
Section: Discussionmentioning
confidence: 99%
“…AF is a common arrhythmia after any type of cardiac sur gery, including CABG surgery or surgical valve replace ment/repair. [204][205][206][207][208][209] Newonset AF in CABG may occur at any point from the time of the procedure, usually 2 to 4 days postoperatively with peak occurrence at 2 days. 206 AF occurs in 28% to 33% of patients undergo ing CABG.…”
Section: Major Cardiac Interventionsmentioning
confidence: 99%
“…82,83,84 Finally, the treatment will be those with hemodynamic compromise, is permeated drains, by performing emergency echocardiography and reoperation. 85,86,87,88,89 …”
Section: Tamponadementioning
confidence: 99%